Crystallinity and optical properties of β-Ga2O3/Ga2S3 layered structure obtained by thermal annealing of Ga2S3 semiconductor. (January 2021) - Sprincean, Veaceslav; Lupan, Oleg; Caraman, Iuliana; Untila, Dumitru; Postica, Vasile; Cojocaru, Ala; Gapeeva, Anna; Palachi, Leonid; Adeling, Rainer; Tiginyanu, Ion; Caraman, Mihail
Abstract: In this work, the β-Ga2 O3 nanostructures were obtained by thermal annealing in air of β-Ga2 S3 single crystals at relatively high temperatures of 970 K, 1070 K and 1170 K for 6 h. The structural, morphological, chemical and optical properties of β-Ga2 O3 –β-Ga2 S3 layered composites grown at different temperatures were investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) as well as photoluminescence spectroscopy (PL) and Raman spectroscopy. The results show that the properties of obtained β-Ga2 O3 –β-Ga2 S3 composites were strongly influenced by the thermal annealing temperature. The XRD and Raman analyses confirmed the high crystalline quality of the formed β-Ga2 O3 nanostructures. The absorption edge of the oxide is due to direct optical transitions. The optical bandwidth was estimated to be approximately 4.34-4.41 eV, depending on the annealing temperature. Annealing of the β-Ga2 S3 monocrystals at a higher temperature of 1170 K showed the complete conversion of the surface to β-Ga2 O3 . These results demonstrate the possibility to grow high quality β-Ga2 O3 –β-Ga2 S3 layered composites and β-Ga2 O3 nanostructures in large quantities for various applications such as gas sensing, non-toxic biomedical imaging, nonlinear optical, as well as power device applications. Micro and nanocrystallites present on the surface of the Ga2 O3 layer contribute to a diffusion of the incident light which leads to an increase of the absorption rate allowing thus to reduce the thickness of the Ga2 O3 layer, in which the generation of unbalanced charge carriers takes place. By decreasing the Ga2 O3 layer thickness in such layered composites, the efficiency of photovoltaic cells based on such junctions can be increased.